Adiland Property Website Design and KPR Management Using the Requirement Prototyping Method - Setyoadi, Eddy Triswanto; Wirapraja, Alexander; Prakoso, Muhammad Adi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
The property business is always in great demand and is discussed by every class of society, that's what makes all business people vying to improve their property business, one of which is by utilizing technology so that it can make it easier for businesses to develop where companies can use technology as a tool. when making a property reservation. In this research, a website-based information system was created that helps Adiland Property Company in improving services in its business. The system created consists of a property booking system and mortgage data processing. The existence of a mortgage data processing system can make it easier for companies to manage mortgage data by customers in an integrated manner, besides that with an online ordering system it can also make it easier for customers to make orders where there are several choices of online payment methods. In making the system, the software development method was used using the requirements prototyping method, while testing this application, two methods have been used, namely blackbox testing. In blackbox testing, testing is carried out by trying all the existing inputs on the system whether they are as expected by giving a questionnaire to each existing user, namely the customer, property agent admin, in-house mortgage manager. The results obtained are a website that can be used by Adiland Property to reach a wider market and ease in making property purchase transactions.